PLZ, WILL PAY ALOT!!!!!!!!!

Algebra
Tutor: None Selected Time limit: 1 Day

Mar 21st, 2015

From the first equation, y = 5x - 5. Substitute this expression into the second equation:

5x - 3(5x - 5) = 15;  5x - 15x + 15 = 15; -10x = 0; x = 0. Finally, y = 5*0 - 5 = -5.

Correct answer: a.

Mar 21st, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Mar 21st, 2015
...
Mar 21st, 2015
Dec 3rd, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer